1999
DOI: 10.1055/s-0037-1614526
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variations in Natural Coagulation Inhibitors Protein C, Protein S and Antithrombin in Healthy Men: A Possible Association with Interleukin-6

Abstract: SummaryRecent observations describe an increase in platelet aggregability and a decrease in fibrinolytic activity in the early morning hours. To determine whether anticoagulant proteins also show such a circadian variation we measured protein C (PC), protein S (PS), antithrombin (AT) and heparin cofactor-II (HC-II) levels on venous plasma samples taken from 10 healthy men at three-hour intervals throughout a 24-hour period. To investigate the possible temporal mapping of circadian periodicity, we also measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Indeed, circadian variations in immunocompetent cells in peripheral blood are of a magnitude to require attention in medical diagnostics [34,35]. Circadian changes in the circulation of T, B, or NK lymphocyte subsets in peripheral blood and in the density of epitope molecules at their surface, which may be related to cell reactivity to antigen exposure, have been reported.…”
mentioning
confidence: 99%
“…Indeed, circadian variations in immunocompetent cells in peripheral blood are of a magnitude to require attention in medical diagnostics [34,35]. Circadian changes in the circulation of T, B, or NK lymphocyte subsets in peripheral blood and in the density of epitope molecules at their surface, which may be related to cell reactivity to antigen exposure, have been reported.…”
mentioning
confidence: 99%
“…Several studies have shown that both the blood coagulation and the fibrinolytic activity are subjected to circadian variations in healthy individuals (Angleton et al , 1989; Kapiotis et al , 1997; Undar et al , 1999). However, again only a limited number of parameters were monitored, and relatively few samples throughout a 24 h period were collected.…”
mentioning
confidence: 99%
“…Protein C is produced by the liver, and a significant circadian variation was found in human plasma with peaks at 6 a. m. [7]. In this study, we determined the circadian rhythm of protein C in plasma in patients with severe autonomic dysfunction, and discussed the usefulness of this method as a marker of autonomic function in liver in such cases.…”
Section: Introductionmentioning
confidence: 96%